2016
DOI: 10.1017/jfm.2016.224
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility effects on the structural evolution of transitional high-speed planar wakes

Abstract: The compressibility effects on the structural evolution of the transitional high-speed planar wake are studied. The relative Mach number (Ma r ) of the laminar base flow modifies two fundamental features of planar wake transition: (i) the characteristic length scale defined by the most unstable linear mode; and (ii) the domain of influence of the structures within the staggered two-dimensional vortex array. Linear stability results reveal a reduced growth (approximately 30 % reduction up to Ma r = 2.0) and a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…As discussed by Leppington [18], if wavelike problems are of interest, the analysis of the intermediate region presented here can be fed into a full calculation of the global flow by matching of this Rayleigh-Jansen solution to a far-field solution at large distances-where the wavelike nature of the compressible flow must be accounted for-and an inner core region near the vortex. This basic theoretical study may also help in understanding compressible wake structures behind bluff bodies where it has recently been indicated that planar models can play a role [7]. A consequence of our analysis is that the aspect ratio 0.28056, which is the isolated value for neutral stability in the incompressible case, is well below the critical value of 0.38187, meaning that making the fluid weakly compressible will speed up a street of small vortices with aspect ratio close to this physically important value.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As discussed by Leppington [18], if wavelike problems are of interest, the analysis of the intermediate region presented here can be fed into a full calculation of the global flow by matching of this Rayleigh-Jansen solution to a far-field solution at large distances-where the wavelike nature of the compressible flow must be accounted for-and an inner core region near the vortex. This basic theoretical study may also help in understanding compressible wake structures behind bluff bodies where it has recently been indicated that planar models can play a role [7]. A consequence of our analysis is that the aspect ratio 0.28056, which is the isolated value for neutral stability in the incompressible case, is well below the critical value of 0.38187, meaning that making the fluid weakly compressible will speed up a street of small vortices with aspect ratio close to this physically important value.…”
Section: Discussionmentioning
confidence: 98%
“…where ν 0 is some constant reference density. Clearly, (4) and (7) together no longer constitute the Cauchy-Riemann equations for harmonic functions φ and ψ. Nevertheless, we continue to define a complex potential [29]…”
Section: The Imai-lamla Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virk et al [13] studied compressible vortex reconnection of two antiparallel vortex tubes, and found that the shocklets induce the earlier occurrence of the vortex reconnection in larger Ma flows, and reduce the reconnection degree and curvature of isosurfaces of the vorticity magnitude. Hickey et al [14] found that the compressibility effects inhibit the streamwise communication and increase the cross-wake communication of neighboring vortices in transitional high-speed planar wakes. In compressible turbulence, a series of studies of Lee et al [15][16][17] showed that shocklets change the vorticity and dilatation distribution in high-Ma turbulent flows, which leads to strong shocklet-vortex interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of core size on compressible hollow vortex streets 821 trying to understand the effects of compressibility on the structural evolution of transitional high-speed planar wakes, with recent work (Hickey, Hussain & Wu 2016) indicating that quasi-two-dimensional planar wakes of the kind examined here have a role to play. The significance of the results herein to such studies has yet to be ascertained.…”
Section: Discussionmentioning
confidence: 92%